Summertime spatiotemporal patterns of nitrogen oxides (NOx) in Salt Lake City - Guevara Proaño, Daniela Carolina, author; Fischer, Emily V., advisor; Collett, Jeffrey L., Jr., committee member; Jathar, Shantanu H., committee member (Colorado State University. Libraries, 2025)
Salt Lake City, UT experiences persistent summertime ozone (O3) exceedances of the National Ambient Air Quality Standard (NAAQS). During the 2024 Salt Lake City-Summer Ozone Study (SLC-SOS), we deployed the Aerodyne dual channel Cavity Attenuated Phase Shift Monitor (CAPS) in a mobile laboratory to quantify regional gradients and daily variability of nitrogen oxides (NOx). Our analysis for smoke-free days include: (1) ambient NOx abundances and NO2/NOx ratios from vehicle plumes compared with nearby urban cities; (2) regional NOx gradients and morning-afternoon differences; and (3) weekday-weekend NOx variability. Compared to other U.S. cities, NOx abundances (7.7 ± 4.4 ppbv) and on-road NO2/NOx plume ratios (11.9 ± 10.3%) are higher than previously reported. Even after filtering near-vehicle emissions, there is a large east-west NOx gradient in NOx. The absolute value is methodologically dependent and varies from > 25 ppbv to ~4 – 5 ppbv. Maximum abundances are located at the Near Road (16.3 ppbv) and Utah Tech (11.7 ppbv) monitoring sites, and the minima are located at the Herriman #3 and Red Butte (< 3ppbv) monitoring sites. On weekday mornings, NOx shows an east-west gradient of about a factor of ~10 between the Near Road and Herriman #3 sites, primarily driven by rush hour traffic. In the afternoon, the highest abundances shift southward, with gradients of ~11 to 50 ppbv (plume isolation method which removes short-lived NOx peaks) under northwesterly winds. High-NOx regions (e.g., Utah Tech, Rose Park, and Copper View) show stronger reduction of ~50 to 80% on weekends compared to low-NOx western regions. These results provide new insights into the spatiotemporal variability of NOx in Salt Lake City to support the mitigation of high O3 levels and improve air quality in the region.
Keywords: regional maps; urban air quality; weekday and weekend; traffic-related air pollution; nitrogen oxides; vehicle emissions